1996
DOI: 10.1128/jvi.70.3.1931-1940.1996
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of herpes simplex virus poly (A) site usage and the action of immediate-early protein IE63 in the early-late switch

Abstract: The essential herpes simplex virus type 1 (HSV-1) immediate-early protein IE63 (ICP27) is pleiotropic in function, promoting the switch from the early to late phase of virus gene expression, and has effects on the posttranscriptional processes of mRNA splicing and 3 processing. We have investigated the role of IE63 in the regulation of viral mRNA 3 processing and of late gene expression. Our in vitro 3 processing studies demonstrated that HSV-1 infection induces an activity, which requires IE63 gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 52 publications
3
49
1
Order By: Relevance
“…The same was observed for UL24.5 which represents an N-terminal truncated isoform of UL24. These data confirm previous findings on differential polyadenylation of selective viral genes during productive infection [23][24][25][26][27] .…”
Section: Rna 3'-end Processing and Export Of Viral Transcriptssupporting
confidence: 92%
See 1 more Smart Citation
“…The same was observed for UL24.5 which represents an N-terminal truncated isoform of UL24. These data confirm previous findings on differential polyadenylation of selective viral genes during productive infection [23][24][25][26][27] .…”
Section: Rna 3'-end Processing and Export Of Viral Transcriptssupporting
confidence: 92%
“…Previous studies reported regulated usage of the 47 viral poly(A) sites during productive infection, which appeared to be mediated or at least influenced by the viral ICP27 protein [23][24][25][26][27][28] . We recently reported that lytic HSV-1 infection results in a widespread but nevertheless selective disruption of transcription termination of host genes 9 .…”
Section: Rna 3'-end Processing and Export Of Viral Transcriptsmentioning
confidence: 94%
“…ICP27 has many roles during the course of the HSV-1 replication cycle. In addition to being necessary for transcription of ␥1 and ␥2 viral genes (79), ICP27 regulates polyadenylation site selection (22,31,55), regulates the intranuclear distribution of splicing factors (52,82), interacts with the export factor Aly/Ref (13), shuttles between the nucleus and cytoplasm (60,69,87), and demonstrates RNA binding activity (59). These functions are consistent with a role of ICP27 in suppressing cellular posttranscriptional processing and transport while promoting viral transcription.…”
Section: Fig 2 Infection With Uv-irradiated Hsv Does Not Results In mentioning
confidence: 75%
“…About half of the human RNAs contain (multiple) alternative poly(A) signals (Edwalds-Gilbert et al, 1997;Tian et al, 2005;Yan and Marr, 2005). Alternative recognition is influenced (1) by intrinsic strength of sequence elements, (2) by the concentration or activity of polyadenylation factors and (3) by tissueor stage-specific regulatory factors (for review see Colgan and Manley, 1997;Barabino and Keller, 1999;Zhao et al, 1999) K IgM heavy-chain pre-mRNA during B-cell differentiation (stage specificity) (Alt et al, 1980;Early et al, 1980;Rogers et al, 1980;Cushley et al, 1982;Takagaki et al, 1996;Phillips et al, 2001Phillips et al, , 2004Veraldi et al, 2001) K Regulated expression of the transcription factor NF-ATc during T-cell differentiation (stage specificity) (Chuvpilo et al, 1999) K LPS stimulation of macrophages results in alternative polyadenylation via upregulation of CstF-64 (Shell et al, 2005) K Calcitonin/calcitonin-related peptide (tissue specificity) (Lou and Gagel, 1998) K Cyclooxygenase 2 (Feng et al, 1993;Ristimaki et al, 1996;Lukiw and Bazan, 1997;Hall-Pogar et al, 2005) K Pancreatitis-associated protein II/regenerating gene III (Honda et al, 2002) K Fanconi anemia group c (FACC) (Strathdee et al, 1992) K Modulation of polyadenylation at weak viral polyadenylation sites in HSV-1-infected cells (McLauchlan et al, 1989(McLauchlan et al, , 1992Sandri-Goldin and Mendoza, 1992;McGregor et al, 1996) K Synthesis of the protein elastin in sun-damaged skin (Schwartz et al, 1998) K NADPH quinone oxidoreductase (Pan et al, 1995) K Set, putative oncogene associated with myeloid leukogenesis (von Lindern et al, 1992) For further detailed and comprehensive survey of mRNAs that undergo alternative poly(A) selection see…”
Section: Alternative Poly(a) Signal (Recognition)mentioning
confidence: 99%